2003
DOI: 10.1159/000070307
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A Induces Apoptosis and Cell Cycle Blockade in Glioblastoma Cell Lines

Abstract: Brefeldin A (BFA), a fungal metabolite known to affect the structure and function of the Golgi apparatus, has recently been shown to induce apoptosis and cell growth inhibition in various human cell lines. Glioblastomas (GB) are cerebral tumors with poor prognosis, which display resistance to current therapies including radio- and chemotherapy. The objective of this study was to investigate BFA effects in three human GB cell lines (SA4, SA146 and U87MG cells). Compared with control cells, about 60% of cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The ability of BFA to induce apoptosis independent of p53 status has also been noted in other types of malignant cells. 74,75 In contrast, Figure 5. Brefeldin A inhibits VEGF secretion.…”
Section: Discussionmentioning
confidence: 89%
“…The ability of BFA to induce apoptosis independent of p53 status has also been noted in other types of malignant cells. 74,75 In contrast, Figure 5. Brefeldin A inhibits VEGF secretion.…”
Section: Discussionmentioning
confidence: 89%
“…As brefeldin A may be toxic to cells (Pommepuy et al, 2003), an experiment was carried out to determine the optimum time of incubation after adding brefeldin A. Cells from 5 normal human donors were incubated for 6 h with CEF or PPD, then for a further 6 h or 18 h with brefeldin A.…”
Section: Resultsmentioning
confidence: 99%
“…BFA treated cells failed to express MT1-MMP on the cell surface and showed increased GRP78 expression, suggesting that abrogated protein trafficking leads to ERSR activation. Pommepuy et al observed increased apoptotic glioma cell death after exposure to BFA [102] (Fig. 2).…”
Section: Targeting Ersr With Small Molecules To Cause Cell Deathmentioning
confidence: 93%
“…The accumulation of these unshuttled proteins in the ER activates ERSR [100, 101]. Apoptosis has been shown to occur in glioma cells following BFA treatment [102]. BFA has also been investigated in glioma cells and shown to downregulate membrane type 1 matrix metalloproteinase (MT1-MMP), an enzyme involved in glioma invasion and metastasis [103].…”
Section: Targeting Ersr With Small Molecules To Cause Cell Deathmentioning
confidence: 99%